Sacroiliac Joint Fusion vs. Conservative Management for Chronic Sacroiliac Joint Pain: A Systematic Review of Pain and Functional Outcomes - I Made Wahyu Adi Putrawan; I Gusti Ngurah Paramartha Wijaya Putra (The Indonesian Journal of General Medicine, 2025)
Introduction: Chronic sacroiliac (SI) joint pain is a significant contributor to low back pain, affecting 15-30% of patients. While conservative management is the initial treatment, many patients fail to achieve lasting relief. Minimally invasive sacroiliac (MIS) joint fusion has emerged as a promising alternative. This systematic review aims to synthesize high-level evidence on the comparative efficacy of MIS fusion versus conservative management for chronic SI joint pain. Methods: Following PRISMA guidelines, a systematic search was conducted across multiple databases. Included studies were randomized controlled trials and cohort studies from the last decade that compared MIS fusion with non-operative care in adults with confirmed SI joint pain. The primary outcomes analyzed were pain reduction (e.g., VAS) and functional improvement (e.g., Oswestry Disability Index). Twenty-seven studies met the inclusion criteria. Results: The evidence consistently demonstrated that MIS fusion provides statistically significant and clinically meaningful improvements in pain and function compared to conservative management. Pain scores (VAS) were reduced substantially more in fusion groups, and functional (ODI) scores showed marked improvement. These benefits were shown to be durable at follow-ups of 24 months and beyond. A significant counterpoint was a sham-controlled trial that found no statistical difference between MIS fusion and a sham procedure. Revision rates for MIS fusion were low, typically 1-5%. Conclusion: For appropriately selected patients with chronic SI joint pain refractory to non-operative care, MIS fusion is a significantly effective and durable intervention that offers a high probability of improving pain, function, and quality of life. Its success is contingent upon rigorous diagnosis, and while the procedure is relatively safe, further research is needed to clarify its efficacy against placebo.